Autogenous tensor fascia lata and dermal graft for gap repair of superficial digital flexor tendon in bovines: Clinical, radiological and histopathological study - GUPTA, O P; KUMAR, NAVEEN; SHARMA, A K; SINGH, G R; PARIHAR, N S (The Indian Journal of Animal Sciences, 2013)
Male cow calves (8), 6 to 8 months old, were randomly divided into 2 equal groups 1 and 2. A 2.5 cm long defect was created in superficial digital flexor (SDF) tendon. Autogenous tensor fascia latu and dermal graft were lIsed to fill the defect in groups I1 and 2 respectively. Clinical, radiological and histopathological observations revcaled that both these autografts can be successfully employed in repair of SDF tendon.